Rethinking Peacekeeping, Gender Equality and Collective Security
XVIII, 323 p.
Keywords: This book examines how the Security Council has approached issues of gender equality since 2000. Written by academics, activists and practitioners the book challenges the reader to consider how women's participation, gender equality, sexual violence and the prevalence of economic disadvantages might be addressed in post-conflict communities.